2017
DOI: 10.1021/acs.biochem.7b00910
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Biochemical Investigation of PglF from Campylobacter jejuni Reveals a New Mechanism for a Member of the Short Chain Dehydrogenase/Reductase Superfamily

Abstract: Within recent years it has become apparent that protein glycosylation is not limited to eukaryotes. Indeed, in Campylobacter jejuni, a Gram negative bacterium, more than 60 of its proteins are known to be glycosylated. One of the sugars found in such glycosylated proteins is 2,4-diacetamido-2,4,6-trideoxy-α-d-glucopyranose, hereafter referred to as QuiNAc4NAc. The pathway for its biosynthesis, initiating with UDP-GlcNAc, requires three enzymes referred to as PglF, PglE, and PlgD. The focus of this investigatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 45 publications
0
31
0
Order By: Relevance
“…We also showed that the insertion of the pen-pal and pglF genes into the amyE locus of the Δ spsM mutant strain restored Leg production. Pen-Pal and PglF were previously shown to convert UDP-GlcNAc to UDP-4-keto-6-deoxy-GlcNAc ( 43 , 49 ). More surprisingly, the addition of the legB gene in the Δ spsM mutant strain did not fully restore Leg production.…”
Section: Discussionmentioning
confidence: 99%
“…We also showed that the insertion of the pen-pal and pglF genes into the amyE locus of the Δ spsM mutant strain restored Leg production. Pen-Pal and PglF were previously shown to convert UDP-GlcNAc to UDP-4-keto-6-deoxy-GlcNAc ( 43 , 49 ). More surprisingly, the addition of the legB gene in the Δ spsM mutant strain did not fully restore Leg production.…”
Section: Discussionmentioning
confidence: 99%
“…The final step is the transfer of the proton from the conserved glutamate back to C‐5′ and transfer of the hydride from NADH to C‐6′ to yield the final product. A recent report has shown that the tyrosine residue is not strictly conserved, however, and a different catalytic mechanism has been put forth which does not invoke the use of a tyrosinate base …”
Section: Discussionmentioning
confidence: 99%
“…A buffered solution of 50 mM UDP-GlcNAc was prepared in 50 mM HEPPS (pH 8.0). To this solution, 20 mg/ml of PglF, a UDP- N -acetyl-glucosamine 4,6-dehydratase from C. jejuni , was added ( 8 ). The reaction was allowed to proceed overnight at room temperature.…”
Section: Methodsmentioning
confidence: 99%